Efficacy of the Combination of Tachyplesin III and Clarithromycin in Rat Models of Escherichia coli Sepsis - Cirioni, Oscar (American Society for Microbiology (ASM), 2008)
We investigated the efficacy of tachyplesin III and clarithromycin in two experimental rat models of severe gram-negative bacterial infections. Adult male Wistar rats were given either (i) an intraperitoneal injection of 1 mg/kg Escherichia coli 0111:B4 lipopolysaccharide or (ii) 2 × 10(10) CFU of E. coli ATCC 25922. For each model, the animals received isotonic sodium chloride solution, 1 mg/kg tachyplesin III, 50 mg/kg clarithromycin, or 1 mg/kg tachyplesin III combined with 50 mg/kg clarithromycin intraperitoneally. Lethality, bacterial growth in the blood and peritoneum, and the concentrations of endotoxin and tumor necrosis factor alpha (TNF-α) in plasma were evaluated. All the compounds reduced the lethality of the infections compared to that for the controls. Tachyplesin III exerted a strong antimicrobial activity and achieved a significant reduction of endotoxin and TNF-α concentrations in plasma compared to those of the control and clarithromycin-treated groups. Clarithromycin exhibited no antimicrobial activity but had a good impact on endotoxin and TNF-α plasma concentrations. A combination of tachyplesin III and clarithromycin resulted in significant reductions in bacterial counts and proved to be the most-effective treatment in reducing all variables measured.